Diet cues and their utility for risk assessment in degraded habitats. (June 2019) - McCormick, Mark I.; Ferrari, Maud C.O.; Fakan, Eric P.; Barry, Randall P.; Chivers, Douglas P.
Abstract : The change in coral reefs from live coral to algal-dominated seascapes prevents some fish species from using chemical alarm cues to gain information about their risk of predation. Field experiments showed that Ambon damselfish, Pomacentrus amboinensis, were able to learn the identity of individual novel predators from a cocktail of odours from three predators derived from digestive products. Learning only occurred when the predators had been fed conspecifics of the prey species in the presence of water that had passed over live hard coral. This allows novel predators to be identified long after the immediate capture and ingestion event. Fish that had the same learning opportunity in degraded water took more risk and died faster on habitat patches in the field. Ambon damselfish respond to chemical alarm cues from closely related Pomacentrus nagasakiensis, in both live and degraded water, yet experiments suggested they cannot use the congeneric diet odours to label predators. However, we did find a modest survival benefit under natural conditions, suggesting some limited learning occurred. Findings suggest that as coral habitats degrade, fishes that are affected by the changing chemistry will have a greatly reduced range of mechanisms for obtaining and updating threat information, altering the resilience of communities. Highlights: Risk assessment of fishes can change when coral reefs become degraded. Some species can no longer use chemical alarm cues to inform, learn and update risk. Diet odours from predators were a useful way of labelling novel predator smells. Diet odours only worked in live coral water and not water from degraded coral. Fish conditioned on degraded coral took more risks and died faster in the field.